Organophosphorus Nerve Agents: Types, Toxicity, and Treatments - Sudisha Mukherjee; Rinkoo Devi Gupta (Journal of Toxicology)
Organophosphorus compounds are extensively used worldwide as pesticides which cause great hazards to human health. Nerve agents, a subcategory of the organophosphorus compounds, have been produced and used during wars, and they have also been used in terrorist activities. These compounds possess physiological threats by interacting and inhibiting acetylcholinesterase enzyme which leads to the cholinergic crisis. After a general introduction, this review elucidates the mechanisms underlying cholinergic and noncholinergic effects of organophosphorus compounds. The conceivable treatment strategies for organophosphate poisoning are different types of bioscavengers which include stoichiometric, catalytic, and pseudocatalytic. The current research on the promising treatments specifically the catalytic bioscavengers including several wild-type organophosphate hydrolases such as paraoxonase and phosphotriesterase, phosphotriesterase-like lactonase, methyl parathion hydrolase, organophosphate acid anhydrolase, diisopropyl fluorophosphatase, human triphosphate nucleotidohydrolase, and senescence marker protein has been widely discussed. Organophosphorus compounds are reported to be the nonphysiological substrate for many mammalian organophosphate hydrolysing enzymes; therefore, the efficiency of these enzymes toward these compounds is inadequate. Hence, studies have been conducted to create mutants with an enhanced rate of hydrolysis and high specificity. Several mutants have been created by applying directed molecular evolution and/or targeted mutagenesis, and catalytic efficiency has been characterized. Generally, organophosphorus compounds are chiral in nature. The development of mutant enzymes for providing superior stereoselective degradation of toxic organophosphorus compounds has also been widely accounted for in this review. Existing enzymes have shown limited efficiency; hence, more effective treatment strategies have also been critically analyzed.